Réponses

  • Cetb
  • Modérateur confirmé
2013-09-23T13:23:55+02:00
2x+3=7(x-4)+6
2x+3=7x-28+6
2x-7x=-28+6-3
-5x=-25
x=25/
x=5

7(2x+3)-6=3x-2(4x-7)
14x+21-6=3x-8x+14
14x-3x+8x=14+6-21
19x=-1
x=-1/19

(5x+15)(2x-7)=0
un produit de facteur est nul si et seulement si l'un de ses facteurs au moins est nul.
Soit 5x+15=0   soit 2x-7=0
5x+15=0
5x=-15
x=-15/5
x=-3

2x-7=0
2x=7
x=7/2
2013-09-23T14:05:26+02:00
2x+3=7(x-4)+6=2x+3=7x-28+6
2x-7x=-28+6-3
-5x=-25
x=5

7(2x+3)-6=3x-2(4x-7)
14x+21-6=3x-8x+14
14x-3x+8x=14-21+6
19x=-1
x=-1/19

(5x+15)(2x-7)=0
10x²-35x+30x-105=0
10x²-5x-105=0